PENGARUH SISTEM AKUNTANSI KEUANGAN DAN AKSESIBILITAS LAPORAN KEUANGAN TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kota Payakumbuh) - Lily -; Muhammad Rasuli; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of the financial accounting system and accessibility of financial statements on the accountability in financial management. This study was conducted at SKPD of Payakumbuh city. The population in this study were employed who worked in the SKPD Payakumbuh city (25 government agencies). The sampling method used in this study is purposive sampling method. The respondent in this study is the head of SKPD, the head of financial, treasurer of SKPD and financial staff is a side direct related in the financial management area on government of Payakumbuh city. The sample used in this study were 100 respondents. The hypotheses then tested is multiple linear regression analysis by using SPSS version 20.0.The result of this study indicated that the financial accounting system and accessibility of financial statements influence on the accountability in financial management area. The magnitude of the effect (R2) financial accounting system, accessibility of financial statements on the accountability in financial management area was 31,9%. While the remaining 68,1% is influenced by other independent variabel that are not observed in this study.Keywords : Accountability, financial, management, accounting, and accessibility